Aplikasi Customer Relationship Management (CRM) Berbasis Web Pada PT. Utomo International - Muhammad Fakhrur Rozi; Samsoni (CV. Multi Kreasi Media, 2023)
PT. Utomo International is an APM (Brand Holder Agent), namely a company that has exclusive rights to import, distribute and sell automotive products with the Royal Alloy, NIU, Italjet and Energica brands in Indonesia, and is the only agent recognized by the brand owner. At this time the condition of the system that is running is still not good because it still uses a system that has not been computerized, namely storing customer prospect data obtained by sales still using notes on paper and in each sales book so that the risk of data loss is still very large, prospect data that is even sales can still not be maximized properly. This web-based Customer Relationship Management (CRM) application is expected to be able to fix existing problems and be able to store customer prospect data which can be accessed anywhere and anytime via a browser and the internet.